1992
DOI: 10.1177/154079699201700110
|View full text |Cite
|
Sign up to set email alerts
|

Functional Life Skills, Academic Skills, and Friendship/Social Relationship Development: What Do Parents of Students with Moderate/Severe/Profound Disabilities Value?

Abstract: A pilot study was conducted to verify empirically the educational activitypreferences of68 parents ofstudents with moderate and severe/profound mental disabilities. Parents were surveyed to determine the relative value they place on the three areas offunctional life skills, academic skills, and friendship/social relationship development in the educational programs of their sons/ daughters. Parents ofstudents withmoderate disabilities ratedfunctional life skills most highly, while parents of students with sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The importance of social skill development as an educational program outcome was emphasized by the parents (Hamre-Nietupski et al, 1992;Kolb & Hanley-Maxwell, 2003). In the study of Giangreco, Dennis et al (1993b), the benefits of inclusion identified by parents were increasing personal enjoyment and friendship, appreciating individual differences among people, enhancing social/ emotional growth, and broadening their children's personal experiences.…”
Section: Parents' Views Of Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of social skill development as an educational program outcome was emphasized by the parents (Hamre-Nietupski et al, 1992;Kolb & Hanley-Maxwell, 2003). In the study of Giangreco, Dennis et al (1993b), the benefits of inclusion identified by parents were increasing personal enjoyment and friendship, appreciating individual differences among people, enhancing social/ emotional growth, and broadening their children's personal experiences.…”
Section: Parents' Views Of Inclusionmentioning
confidence: 99%
“…were more important outcomes than the health benefits (Wilson, 1999;Hamre-Nietupski, et al, 1992). The process of making and retaining friendships that appears to come automatically to most children is not always the case for children with disabilities (Goodwin & Watkinson, 2000).…”
Section: Andrea Explainedmentioning
confidence: 99%
“…Furthermore, some parents do not seem to be aware of the importance of skill differentiation based on age. Neither Epps and Myers (1989) nor Hamre-Nietupski et al (1992) found any differential results with regard to curriculum desires related to the age of the parents' children. This seems curious, as one might expect that parents would want a change in curricular emphases as their children grow older.…”
Section: What Do Parents Want Their Children To Learn?mentioning
confidence: 86%
“…First, instructional goals for children vary with age and degree of severity. Parents desire different services and have different concerns based on the ages of their children and the severity of their disability (D'Amato & Yoshida, 1991;Epps & Myers, 1989;Hamre-Nietupski, Nietupski, & Strathe, 1992). Most parents seem to believe that instruction in functional skills, perhaps especially domestic and vocational skills, is most relevant for their children.…”
Section: What Do Parents Want Their Children To Learn?mentioning
confidence: 97%
See 1 more Smart Citation